2022
DOI: 10.3390/en15228696
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Characteristics and Resource Potential of Marine Shale in South China: A Review

Abstract: Many sets of Paleozoic marine organic-rich shale strata have developed in South China. However, the exploration and development results of these shale formations are quite different. Based on the data of core experiment analysis, drilling, fracturing test of typical wells, the reservoir differences and controlling factors of four sets of typical marine organic-rich shale in southern China are investigated. The four sets of shale have obvious differences in reservoir characteristics. Ordovician–Silurian shale m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…These two types of quartz are typically surrounded by clay minerals, which are mechanically unstable, leading to lower brittleness in shale samples with high QCI values. Previous studies found that biogenic quartz has a smaller Poisson’s ratio and a lower compressive strength than other types of quartz, demonstrating better fracability. It is worth noting that compared to middle-shallow shale gas reservoirs, deep-burial shale reservoirs experience high temperatures (>100 °C) and high pressures (>90 MPa), resulting in significant changes in the mechanical properties of shale reservoirs. Under these geological conditions, the plasticity of minerals within rocks increases, and even carbonate minerals (e.g., calcite) can undergo plastic transformation. , As the depth of burial increases, the mechanical response of deep shale becomes weaker than that of middle-shallow shale, primarily due to the influence of higher stress levels.…”
Section: Resultsmentioning
confidence: 99%
“…These two types of quartz are typically surrounded by clay minerals, which are mechanically unstable, leading to lower brittleness in shale samples with high QCI values. Previous studies found that biogenic quartz has a smaller Poisson’s ratio and a lower compressive strength than other types of quartz, demonstrating better fracability. It is worth noting that compared to middle-shallow shale gas reservoirs, deep-burial shale reservoirs experience high temperatures (>100 °C) and high pressures (>90 MPa), resulting in significant changes in the mechanical properties of shale reservoirs. Under these geological conditions, the plasticity of minerals within rocks increases, and even carbonate minerals (e.g., calcite) can undergo plastic transformation. , As the depth of burial increases, the mechanical response of deep shale becomes weaker than that of middle-shallow shale, primarily due to the influence of higher stress levels.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, lithofacies division determines the high-quality reservoir of the Longmaxi Formation. The dominant lithofacies of the Longmaxi Formation is siliceous shale, which has the highest reservoir quality and the most developed OM pore network (Jia et al, 2021;Wang et al, 2022;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%